THE THIRD RENAISSANCE - EDUCATION AND DEVELOPMENT: PAST, PRESENT AND FUTURE - Xoshimova Dilnoza Sobit qizi (Лучшие интеллектуальные исследования, 2023)
Annotation: In this article, the contributions of the representatives of the highly spiritual generation, the scientists and scholars who lived through the first and second renaissance to science, education and upbringing, as well as their indelible comments, are highlighted. In addition, the prospects of educational development, the importance of education in human life, inculcating the concept of value, which is the highest blessing, into the minds of young people, raising them spiritually and physically healthy is the main way.